Tomada de decisão gerencial sob uma modalidade não convencional (Ágora de Heterodoxias, 2023)
This article starts from the following premise: management is an essentially practical activity, therefore, in its daily execution, new skills are acquired for use in managerial action. In this sense, pragmatism is assumed as the philosophical foundation of the managerial profession. One of the essential functions of managers in organizations is decision-making, so every manager aims to decide correctly. However, in the decision-making process, success cannot be envisioned. What is usually done is to observe its implementation, monitor its development and evaluate its impacts and results. It should be noted that managers make decisions in complex contexts, with incomplete information, in unstructured situations and with time constraints. Under these circumstances, the classical rational instrumental model for decision making is incomplete and inadequate, as it is based on the premise that the decision maker has complete and perfect information. This, as you know, is not possible. Given the limited scope of the instrumental rational model, the manager seeks to use all his available capacities and resorts to different schemes in decision-making. Among the non-conventional factors that the manager uses to make decisions, there is intuition, so we will see how this variable is suitable for the manager when making a decision.
Keywords: tomada de decisão; racional; Intuição